Feminism and Generational Conflicts in Alexa Hennig von Lange’s Relax, Elke Naters’s Lügen, and Charlotte Roche’s Feuchtgebiete - Margaret McCarthy (Studies in 20th & 21st Century Literature, 2011)
The publication of Charlotte Roche’s controversial novel Feuchtgebiete, along with a wave of nonfiction popfeminist writings, prompted heated debates in 2008 among different generations of German feminists. Despite their attempts to call attention to historically persistent forms of sexism, popfeminists quite emphatically distanced themselves from Alice Schwarzer, the face of German feminism for over thirty-five years. Yet casting themselves as rebels who break away from Schwarzer’s second-wave feminism has necessitated that they suppress affinities and shared blind spots in order to underscore their ostensibly less dogmatic, more fun approach. Feuchtgebiete, Alexa Hennig von Lange’s Relax and Elke Naters’s Lügen depict generational conflicts in terms of fraught bonds between mothers and daughters, a dynamic which sheds light on these tensions among feminists. This essay highlights the coexistence in each novel of a pop sensibility with aspects of contemporary and historical feminism. If the former feeds highly individual choices and signifying acts, the latter points to a collective identity and social movement. As much as the protagonists experience the chasm between these two poles, they also point to forward-thinking ways of re-conceptualizing feminism.
Keywords: Charlotte Roche; Feuchtgebiete; popfeminist; sexism; Alice Schwarzer; second-wave feminism; Hennig von Lange; Relax; Elke Naters; Lügen; contemporary feminism; historical feminism; feminism; collective identity